Green Intellectual Capital As a Catalyst: Synergizing Competitive Strategy And Carbon Disclosure For Firm Performance - Nurnelisa, Nurnelisa (AKTSAR: Jurnal Akuntansi Syariah, 2026)
The global shift towards a low-carbon economy has pressured Indonesian firms to integrate environmental stewardship into their core strategies. This study aims to investigate the influence of Sustainability Committee, Competitive Business Strategy, and Carbon Emission Disclosure on the financial performance of JII70-listed companies from 2020 to 2024, with a specific focus on the moderating role of Green Intellectual Capital (GIC). Utilizing panel data and Moderated Regression Analysis (MRA), the results reveal that Competitive Business Strategy and Carbon Emission Disclosure significantly enhance Return on Assets (ROA), while Sustainability Committees remain largely symbolic. A unique finding of this research is that GIC serves as a powerful "strengthening" moderator, transforming environmental transparency and asset efficiency into superior economic returns. This suggests that internal knowledge-based green assets are essential for translating sustainability efforts into competitive financial advantages in the Sharia capital market.